Accounting Conservatism and Domestic Market Obligation on Coal Company’s Profitability: The Moderating Effect of Institutional Ownership Structure - Oxaria Silviana Devi; Sri Suryaningsum; Sutoyo (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to investigate the impact of conservative accounting practices and coal Domestic Market Obligation (DMO) on corporate profitability, while also examining how the institutional ownership structure moderates the relationship between conservative accounting, coal DMO, and corporate profitability. A sample of balanced data was collected from the 25 most active coal mining companies listed in Indonesia Stock Exchange (IDX) between 2019 and 2025 with 102 observations. The research employs quantitative methods to test the formulated hypotheses regarding the relationships among conservative accounting, coal DMO, institutional ownership, and corporate profitability. Panel regression models were used for data analysis. Accrual method is used as a benchmark for measuring accounting conservatism. The corporate performance indicators used in this study are return on assets (ROA) and return on equity (ROE) representing profitability. The results of the research show that accounting conservatism has no effect on profitability (ROA and ROE), coal DMO has a significant positive effect on profitability (ROA and ROE), and institutional ownership structure variables can moderate accounting conservatism and coal DMO on profitability (ROA and ROE). This research contributes to the existing literature by providing empirical evidence on the interplay between accounting practices, regulatory frameworks, and ownership structures within the coal mining sector. The findings underscore the importance of institutional ownership in shaping corporate strategies and financial outcomes, offering valuable insights for stakeholders in the industry, including investors and policymakers.